Metabolic characteristics of 13‐cis‐retinoic acid (isotretinoin) and anti‐tumour activity of the 13‐cis‐retinoic acid metabolite 4‐oxo‐13‐cis‐retinoic acid in neuroblastoma. (December 2014) - Sonawane, Poonam; Cho, Hwang Eui; Tagde, Ashujit; Verlekar, Dattesh; Yu, Alice L; Reynolds, C Patrick; Kang, Min H
<x xml:space="preserve">Abstract</x> Background and Purpose Isotretinoin (13‐cis‐retinoic acid; 13‐cRA) is a differentiation inducer used to treat minimal residual disease after myeloablative therapy for high‐risk neuroblastoma. However, more than 40% of children develop recurrent disease during or after 13‐cRA treatment. The plasma concentrations of 13‐cRA in earlier studies were considered subtherapeutic while 4‐oxo‐13‐cis‐RA (4‐oxo‐13‐cRA), a metabolite of 13‐cRA considered by some investigators as inactive, were greater than threefold higher than 13‐cRA. We sought to define the metabolic pathways of 13‐cRA and investigated the anti‐tumour activity of its major metabolite, 4‐oxo‐13‐cRA. Experimental Approach Effects of 13‐cRA and 4‐oxo‐13‐cRA on human neuroblastoma cell lines were assessed by DIMSCAN and flow cytometry for cell proliferation, MYCN down‐regulation by reverse transcription PCR and immunoblotting, and neurite outgrowth by confocal microscopy. 13‐cRA metabolism was determined using tandem MS in human liver microsomes and in patient samples. Key Results Six major metabolites of 13‐cRA were identified in patient samples. Of these, 4‐oxo‐13‐cRA was the most abundant, and 4‐oxo‐13‐cRA glucuronide was also detected at a higher level in patients. CYP3A4 was shown to play a major role in catalysing 13‐cRA to 4‐oxo‐13‐cRA. In human neuroblastoma cell lines, 4‐oxo‐13‐cRA and 13‐cRA were equi‐effective at inducing neurite outgrowth, inhibiting proliferation, decreasing MYCN mRNA and protein, and increasing the expression of retinoic acid receptor‐β mRNA and protein levels. Conclusions and Implications We showed that 4‐oxo‐13‐cRA is as active as 13‐cRA against neuroblastoma cell lines. Plasma levels of both 13‐cRA and 4‐oxo‐13‐cRA should be evaluated in pharmacokinetic studies of isotretinoin in neuroblastoma.